(untitled) (Proceeding of Saizu International Conference on Transdisciplinary Religious Studies, 2023)
Understanding Islam by using various approaches or perspectives of a scientific discipline is very possible, in fact it must be done because Islam, with its main source of teachings contained in the Qur’an and as Sunnah, does not only talk about matters of faith, worship, morals and the afterlife. , but talking about science, technology, history, social, education, politics, economy, culture, art and so on. Islam places politics as a way of looking after the affairs of the people (ri’ayah syu-un al-ummah). Islam and politics cannot be separated, because Islam without politics will give birth to shackled Muslims who do not have the freedom and independence to implement Islamic law. By using a political approach in Islamic Studies, we can understand that Islam is not only a monolithic doctrine, but also a doctrine that can influence the policies of the rulers to gain the benefit of the people. Several political approaches in Islamic studies include: the De-confessionalization Approach, the Domestication of Islam approach, the schismatic flow approach, the Trichotomy Approach, and the Cultural Islam Approach.